Contribution to the sand fly fauna (Diptera: Phlebotominae) of Rio Grande do Sul, Brazil and Leishmania (Viannia) infections - Onilda Santos da Silva; Jörg Grunewald (Memorias do Instituto Oswaldo Cruz, 1999)
American cutaneous leishmaniasis (ACL) is endemic in the State of Rio Grande do Sul, Brazil. As reports of nearby hospitals suggest, the Parque Estadual do Turvo seems to serve as a source for the disease. During three months from November 1996 to February 1997 we collected, in this park, 2,228 sandflies (10 Lutzomyia species and 2 6species). We applied the polymerase chain reaction to 920 females which belong to the following species: Lutzomyia migonei, Lu. pessoai, Lu. fischeri, Lu. misionensis, Lu. lanei, Lu. neivai, Lu. shannoni, and Lu. monticola, in an attempt to verify natural infection by Leishmania (Viannia), the causative agent of ACL. Le. (Viannia) infections were demonstrated by DNA amplification from two Lu. pessoai and one Lu. misionensis female. Lu. pessoai have been found with leptomonas in the gut believed to be Le. (V.) braziliensis in other endemic areas of northeastern and southeastern Brazil. However, Lu. misionensis has never been found carrying a natural infection of Le. (Viannia).